Построение эволютного зацепления - Носко, П. Л.; Черников, А. В.; Павлов, А. И. (НТУ "ХПИ", 2009)
Розглядаються варіанти побудови передач з еволютним зачепленням, яке характеризується тим, що лінія зачеплення має еволюту. Вид еволютного зачеплення залежить від початкових умов (кута зачеплення в полюсі передачі) та величини коефіцієнту різноманітності.

Variants of construction of the evolute gearings which is characterized by that the line of gearing has an evolute are considered. The kind of the evolute gearings depends on entry conditions (a corner of gearing in a pole of transfer) and size of factor of a version.
Keywords: зубчатое зацепление; линия зацепления; контур зуба; коэффициент разновидности